A longitudinal case study of changes in students' attitudes, participation, and learning in collaborative writing. (June 2019) - Chen, Wenting; Yu, Shulin
Abstract: While research about group interactions during second language (L2) or foreign language (FL) collaborative writing has received considerable attention over the last decade, little is known about the role that individual factors like learner attitude plays in affecting patterns of interaction in collaborative writing. This case study aims to investigate how the change of student attitudes affects patterns of interaction and language learning opportunities in collaborative writing and the factors that influence learners' attitudes towards collaborative writing. Analyses of multiple sources of data (pre and post-task interviews, stimulated recall interviews, pre and post-task surveys, reflective journals, pair talk) from two cases of Chinese students across three tasks reveal that changes in students' attitudes towards collaborative writing affected group patterns of interaction, quantity of language-related episodes (LREs) and quality of engagement in solving the LREs. This study also found that English-learning beliefs and experiences, perceived value of peer assistance, and group friendships or dynamics were three major factors that shape students' attitudes towards collaborative writing. This study makes several recommendations for how to best implement collaborative writing tasks in L2 classes to maximize the occasions for language learning.